SENYAPAN DAN KILIR LIDAH PADA DEBAT CAWAPRES 2024 - Natasya Aisyiyah Dzikrillah; Anys Melina; Fahrudin Eko Hardiyanto; Etika Widi Utami (Fakultas Keguruan dan Pendidikan Universitas Muhammmadiyah Bengkulu, 2025)
Silence is a mental process in producing speech. It usually occurs when someone is having a conversation and needs additional time to describe what they want to convey in spoken form. This study aims to identify silences that occurred in the 2024 vice presidential debate. In addition to looking for silences, in this study, we also examined the vice presidential candidates' speech errors in the form of slips of the tongue. A slip of the tongue itself can be defined as a phenomenon in speech production where the speaker